Achalasia: treatment, current status and future advances - Swanström, Lee L. (Korean J Intern Med, 2019)
Achalasia was first described in the 17th century and its treatment continues to be challenging. Palliative treatment involves disruption of the lower esophageal sphincter, which can be accomplished mechanically (balloon dilation or surgical myotomy) or chemically (Botox). True surgical treatment originated some 100 years ago and remained largely unchanged until the advent of thoracoscopic and then laparoscopic myotomy beginning in the 1980s. Because these procedures provided relatively definitive treatment and were well tolerated by patients, minimal invasive surgery assumed a primary role in the treatment algorithms for achalasia. In 2008, an endoscopic (incision-less) myotomy approach, per-oral endoscopic myotomy, was described. This even less invasive approach has rapidly been adopted in the majority of high-volume achalasia centers. Newer interventions, such as stenting and cell transplant, are under active investigation.